1989
DOI: 10.7164/antibiotics.42.470
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylblasticidin S and blasticidin S from Streptomyces setonii culture A83094.

Abstract: In our preceding paperx) we described the isolation and structure elucidation of antibiotic A83094A(16-deethylindanomycin) from the biomass of Streptomyces setonii. The culture filtrate from a fermentation of this same organism contains two broad-spectrum antibiotics which were isolated and determined to be 5-hydroxymethylblasticidin S (A83094B) and blasticidin S (A83094C) as shown in Fig. 1.The flow diagram for the isolation of 5-hydroxymethylblasticidin S and blasticidin S as a complex is presented in Fig. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…Although BS is most potent as an antifungal agent, it also exhibits antibacterial (32), antiviral (16,17), and antitumor activities (39). Several other peptidyl nucleoside antibiotics have close structural similarities to BS (1,7,15,19,20,36,37); they all consist of a cytosine hexuronic nucleoside unit and a basic amino acid side chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although BS is most potent as an antifungal agent, it also exhibits antibacterial (32), antiviral (16,17), and antitumor activities (39). Several other peptidyl nucleoside antibiotics have close structural similarities to BS (1,7,15,19,20,36,37); they all consist of a cytosine hexuronic nucleoside unit and a basic amino acid side chain.…”
mentioning
confidence: 99%
“…As shown in Figure 2, SDS-PAGE of the purified CGA synthase from the last step (lanes 8 CGA synthase, isolated from S. griseochromogenes, catalyzes the formation of CGA from UDP-glucuronic acid and cytosine in the biosynthesis of the peptide-nucleoside antibiotic BS (14) and is also quite likely involved in the biosynthesis of a number of other known nucleoside antibiotics (1,7,15,19,20,36,37). Functionally, CGA synthase belongs to the family of UDPGTs; although UDP-GTs are common in mammalian metabolism and at least two have been reported for fungi (10,40), they have not been previously reported for a prokaryotic organism.…”
mentioning
confidence: 99%
“…The physicochemical data for BI-S have already been reported in several papers (Otake et al 1966, Takeuchi et al 1958, Yonehara 1984; therefore, we report only those that supplement the reported data (Larsen et al 1989) for H-M-BI-S.…”
Section: Bi-s and H-m-bi-s Were Identified By Means Of Ms And Nmr Datamentioning
confidence: 78%
“…It acts against fungi and bacteria by inhibiting protein synthesis with a mechanism similar to Puromycin (Yonehara 1984). H-M-BI-S has recently been isolated together with B1-S from the culture broth of Streptomyces setonii (Larsen et al 1989).…”
mentioning
confidence: 99%
“…1960년대 이후 환경오염을 줄이고 식물병원성 진균에 의한 피해를 줄일 수 있는 화학 농약 대체 생물 학적 제제를 개발하려는 시도가 이루어져 blasticidin, kasugamycin 등이 실제 방제에 적용되었다. 몇몇의 이차대사물질은 독성 등의 이유로 실용화하지 못하고 있는 실정이다 (Larsen et al, 1989;Hotta, 1996). 이러한 문제점 때문에 방선균 이외의 균을 이용한 식물병 방제제 개발이 시도되었다.…”
unclassified